Isaac Olsen - The First Missionary Among the Sami People in Finnmark - Willumsen, Liv Helene (Nordlit, 2019)
This article deals with Isaac Olsen, a Norwegian who was an itinerant catechist and teacher among the Sami people in Finnmark, Northern Norway. The author claims that Isaac Olsen, as a forerunner to the Sami missionary Thomas von Westen, in fact was the first missionary among the Sami people in Finnmark. Isaac Olsen came to Finnmark just after 1700, learned the Sami language and started his work among the Sami population in Eastern Finnmark. He got to know the Sami people well, and they gave him information about Sami pre-Christian religious practice, among other names of places of sacrifice. These names, in addition to many other pieces of information, were written down by Isaac Olsen in a copybook that has been preserved. The article discusses in great detail the contents of this book, which contains valuable knowledge about Early Modern Sami culture and religion. Isaac Olsen, also as a pioneer, translated Danish religious texts into the Sami language, called to Copenhagen to perform translation work by the Missionary College.